2007
DOI: 10.1177/0042085906293927
|View full text |Cite
|
Sign up to set email alerts
|

Promising Strategies for Attracting and Retaining Successful Urban Teachers

Abstract: In the debate about urban school effectiveness and teacher quality, one proposition has emerged as indisputable: The success of urban schools depends heavily on the quality of the teachers who serve the schools and the administrators who support the teachers. Unfortunately, urban school district recruitment policies are often not aligned with research and practical knowledge about urban teacher effectiveness; thus, the best candidates are often ignored, neglected, or otherwise discouraged. To achieve challengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 14 publications
(11 reference statements)
0
27
0
Order By: Relevance
“…Educational institutions that train teachers carry out their programs to prepare prospective teachers for the teaching profession in the best way . To understand prospective teachers' targets associated with their initial occupational targets, motivation for choosing teaching and teaching profession can help educators and policy-makers in improving teacher employment and quality Stotko, Ingram and Beaty-O'Ferrall, 2007;Watt and Richardson, 2007). Because, nowadays, teachers are faced with many situations that reduce their quality of life and cause them to be anxious.…”
Section: Introductionmentioning
confidence: 99%
“…Educational institutions that train teachers carry out their programs to prepare prospective teachers for the teaching profession in the best way . To understand prospective teachers' targets associated with their initial occupational targets, motivation for choosing teaching and teaching profession can help educators and policy-makers in improving teacher employment and quality Stotko, Ingram and Beaty-O'Ferrall, 2007;Watt and Richardson, 2007). Because, nowadays, teachers are faced with many situations that reduce their quality of life and cause them to be anxious.…”
Section: Introductionmentioning
confidence: 99%
“…Teacher enthusiasm for teaching and learning appears to improve learning by increasing student motivation (Patrick et al 2000) while teacher caring appears to impact in a similar manner (Patrick et al 2000;Stronge 2007;Peart and Campbell 1999). There is also evidence that some of these qualities-notably, a commitment to professional growth and enthusiasm-have a particularly positive impact on students in the most disadvantaged schools (Stotko et al 2007).…”
Section: Identifying the Effective Teacher In The Studymentioning
confidence: 99%
“…Their research suggested that districts invest primarily in networks of support for inner-city teachers and use financial incentives as a secondary recruitment tool. Stotko, Ingram, and Beaty-O'Ferrall (2007) studied the motivation behind teachers' decisions to teach in inner-city schools. They observed that altruism was a strong motivator for urban teachers and teacher candidates.…”
mentioning
confidence: 99%
“…Many of their survey respondents indicated that they were drawn to teaching because they wanted to help at-risk students and by doing so make a positive contribution to society. Stotko et al (2007) advised districts to develop recruitment strategies and incentives that emphasized altruism and personal development.…”
mentioning
confidence: 99%
See 1 more Smart Citation